2018
DOI: 10.18502/kls.v4i1.1368
|View full text |Cite
|
Sign up to set email alerts
|

Habit of Smoking Family Members at Home to Successful Smoking Cessation in Indonesia

Abstract: Introduction The percentage of smoking cessation in Indonesia was decreased from 5. 4% (2010) to 4% (2013). This study aims to know the habit of smoking family

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Family support is an important factor for adolescents to stop smoking, one of which is that no single family member smokes. 17 The family role significantly influences the prevention of smoking behavior. 18 Parenting patterns significantly influence smoking behavior in adolescents.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Family support is an important factor for adolescents to stop smoking, one of which is that no single family member smokes. 17 The family role significantly influences the prevention of smoking behavior. 18 Parenting patterns significantly influence smoking behavior in adolescents.…”
Section: Resultsmentioning
confidence: 99%
“…Place a sticker of a smoke-free house and a smoking ban in front of children and pregnant women even if outside the home. 17 The higher the level of family functioning, the higher the self-control of adolescents. 21 Smoking behavior in the house will have a negative impact on the health of family members, smoking habits in the home associated with the incidence of pneumonia in infants.…”
Section: Resultsmentioning
confidence: 99%
“…Indonesia has a national quitline to help smokers quit, but it has not been effective [ 2 , 4 ]. Only 15.7% of smokers have been reported to successfully quit smoking in Indonesia, lower than the corresponding proportions in Korea (41.2%) and South Australia (22.4%) [ 5 ]. Quitting smoking is challenging; prior research found that over 60% of smokers intended to quit and over 40% had attempted to quit [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies in Indonesia found that external factors such as the absence of family members who smoked at home, being informed of household smoking restrictions and the harmful effects of cigarettes, and being unexposed to cigarette advertisements were important factors for successful smoking cessation [ 5 , 8 ]. However, since quitting smoking is a complex behavior, the role of internal factors remains to be clarified.…”
Section: Introductionmentioning
confidence: 99%